The Use of Herbal Medicine in Alzheimer's Disease—A Systematic Review - dos Santos-Neto, Leopoldo Luiz (Oxford University Press, 2006)
The treatments of choice in Alzheimer's disease (AD) are cholinesterase inhibitors and NMDA-receptor antagonists, although doubts remain about the therapeutic effectiveness of these drugs. Herbal medicine products have been used in the treatment of Behavioral and Psychological Symptoms of Dementia (BPSD) but with various responses. The objective of this article was to review evidences from controlled studies in order to determine whether herbs can be useful in the treatment of cognitive disorders in the elderly. Randomized controlled studies assessing AD in individuals older than 65 years were identified through searches of MEDLINE, LILACS, Cochrane Library, dissertation Abstract (USA), ADEAR (Alzheimer's Disease Clinical Trials Database), National Research Register, Current Controlled trials, Centerwatch Trials Database and PsychINFO Journal Articles. The search combined the terms Alzheimer disease, dementia, cognition disorders, Herbal, Phytotherapy. The crossover results were evaluated by the Jadad's measurement scale. The systematic review identified two herbs and herbal formulations with therapeutic effects for the treatment of AD: Melissa officinalis, Salvia officinalis and Yi-Gan San and BDW (Ba Wei Di Huang Wan). Ginkgo biloba was identified in a meta-analysis study. All five herbs are useful for cognitive impairment of AD. M. officinalis and Yi-Gan San are also useful in agitation, for they have sedative effects. These herbs and formulations have demonstrated good therapeutic effectiveness but these results need to be compared with those of traditional drugs. Further large multicenter studies should be conducted in order to test the cost-effectiveness of these herbs for AD and the impact in the control of cognitive deterioration.